PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMAN 1 BANGUN PURBA - -, Pebriani; -, Arcat; Afri, Lusi Eka (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This research aimed to determine the effect of cooperative learning model Student Teams Achievement Division(STAD) to grade students mathematics learning outcomes kelas XI SMAN 1 Bangun Purba. In this study theformulation of the problem is "Is there any type of influence model of Cooperative Learning Student TeamsAchievement Division (STAD) on the results of student learning mathematics classroom XI SMAN BangunPurba?. The object of this study is the result of learning mathematics siawa. Researchers used the test "t" toanalyze the data. From the analysis of data it can be concluded that there is influence of cooperative learningmodel STAD Student Teams Achievement Division on the results of students mathematics learning classroomXI SMAN 1 Bangun Purba School Year.